Felansvar i paketerade fastighetsöverlåtelser - En studie av felansvar, friskrivningar och undersökningsplikt - Johnson,Adam (2024)
Special purpose vehicle (SPV) transactions for real estate is a highly contract regulated field that differs greatly from regular property transactions. This essay investigates the sellers liability for property defects and the buyers duty to investigate, using the legislations applicable on the two different types of transactions. By using mainly written sources of information including laws, law propositions, literature and previous court rulings the essay identifies applicable law for each transaction. This is done through applying the legal dogmatic method to interpret applicable law and legal norms. Because of the low amount of mandatory legislations regarding SPV transactions, the essay finds that there are great practical differences between the two. Therefor the essay utilizes empirical method to conduct interviews with lawyers and experts who come across SPV transactions daily. The two different transactional methods are then compared. Through the investigation of these sources, the essay concludes that there are great differences in regards to the sellers liability for defects. Even though the purpose of the transactions are the same (moving ownership of property), the SPV transactions heavily relies on warranties given by the seller. This differs greatly from the rules regarding liability in Jordabalken, where it’s instead regulated with paragraphs about ”defects in property” (fel I fastighet). The buyers duty to inspect the property before purchase also seems to be missing for SPV transactions, unless prompted by seller. Lastly the sellers possibility to make disclaimers from liability seems to be extensive in comparison.
Keywords: fastighetsrätt; avtalsrätt; associationsrätt; köprätt